Calculation of the Visit Costs of Various Services Provider Groups: Improvement of Payment Mechanisms - Asma Sabermahani; Mohammad Jafari Siriz; Mohsen Barouni (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Initiatives to improve the quality of health services and reduce costs currently have centered around payment mechanisms. In Iran, like many other countries, the outpatient visit costs are paid via fee for service, while real-time visits and other details of provided services are not considered in the tariff setting process. This study attempted to calculate the visit costs of various service provider groups and compared them with tariffs. Methods: In this cross-sectional research, the essential data about different costs were collected from providerschr('39') offices, standard time of each visit was achieved from Iranchr('39')s Ministry of Health and Medical Education, current visit time of service providers was calculated based on health insurance companieschr('39') data across the country. After calculating the standard and current visit costs through the activity-based costing technique, main determinants of costs (major cost centers) were specified for use in probably future weighted tariffs in fee for service payment mechanism. Results: The greatest difference between standard and the current number of visits was found in the Sub-specialist physician group (6784 in a year), and the greatest difference was between standard and current cost of visits in sub-specialist psychiatrists (126703 IRR). Staffing and rental cost centers account for the highest share of total visit cost (87 %). Conclusion: This study demonstrated a significant difference between the current and standard visit costs with tariffs. Therefore, it is essential that policymakers improve the payment mechanism by modifying the visit tariffs for medical service providers. One suggestion in this way is using domestic relative value units according to costing research results.